2021
DOI: 10.3389/fcell.2021.701986
|View full text |Cite
|
Sign up to set email alerts
|

p63 and p53: Collaborative Partners or Dueling Rivals?

Abstract: The tumor suppressor p53 and its oncogenic sibling p63 (ΔNp63) direct opposing fates in tumor development. These paralog proteins are transcription factors that elicit their tumor suppressive and oncogenic capacity through the regulation of both shared and unique target genes. Both proteins predominantly function as activators of transcription, leading to a paradigm shift away from ΔNp63 as a dominant negative to p53 activity. The discovery of p53 and p63 as pioneer transcription factors regulating chromatin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
(125 reference statements)
1
15
0
Order By: Relevance
“…Moreover, we employed the resource to compare the GRN of p53 to its sibling ΔNp63 and, in contrast to previous reports, we demonstrated that ΔNp63 minimally affects any direct p53 target. Instead, a large number of ΔNp63 targets were cell cycle genes, but the mechanistic link between ΔNp63 and the cell cycle remained unclear ( 10 , 32 ). Most recently, TargetGeneReg enabled the discovery of the transcription factor RFX7, an emerging tumor suppressor, as a novel node in the p53 GRN, proposing a mechanism for how p53 regulates several targets ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we employed the resource to compare the GRN of p53 to its sibling ΔNp63 and, in contrast to previous reports, we demonstrated that ΔNp63 minimally affects any direct p53 target. Instead, a large number of ΔNp63 targets were cell cycle genes, but the mechanistic link between ΔNp63 and the cell cycle remained unclear ( 10 , 32 ). Most recently, TargetGeneReg enabled the discovery of the transcription factor RFX7, an emerging tumor suppressor, as a novel node in the p53 GRN, proposing a mechanism for how p53 regulates several targets ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the frequency of p63 positivity is high in squamous cell carcinoma, including in human head and neck squamous cell carcinoma (HNSCC), thymic tumors, urothelial carcinoma, and various salivary gland tumors [ 7 ]. ΔNp63 is known as an oncogenic driver in squamous cell carcinoma and plays an important role in HNSCC cell survival, suppressing p73-dependent apoptosis [ 8 , 9 ]. ΔNp63 can also regulate the expression of genes correlated with epithelial-to-mesenchymal transition (EMT) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another protein that attaches near the CXCL1 gene is p63, a transcription factor from the p53 transcription factor family [ 76 , 77 ]. Both proteins (p53 and p63) induce the expression of different genes, but can also cooperate in the expression of the same genes.…”
Section: Cxcl1: Gene and Transcriptional Regulationmentioning
confidence: 99%